Emotional contagion in voice-to-voice service encounters: a dynamic approach to the influence of customers on employees’ behavior and welfare - Lopes, Maria Rita Rueff Negrão Mendonça (2015)
This thesis focuses on emotional exchange in voice-to-voice interactions and on how customers’ behaviors influence employees’ welfare in this specific context. It comprises one conceptual study and three empirical ones. The first study is a state-of-the-art review of emotional contagion in the service encounter. It provides a comprehensive agenda of methodologies, antecedents, consequences, and different perspectives of the phenomenon in this specific context. It also provides a critical evaluation of existing research, highlighting the key issues and potential insights for prolific research avenues. The second study intends to verify the possibility of emotional contagion to occur in voice-to-voice service settings. More specifically, it aimed to explore one of the emotional contagion propositions that were yet to be tested in this particular setting (the vocal mimicry hypothesis). Not only did we provide evidence supporting this phenomenon, as we also tested for the influence of other variables. Study three sought to validate a Portuguese version of the emotional contagion scale. This scale is a measure of individual differences regarding individuals’ susceptibility to catch emotions. The Portuguese version of the scale yielded good results regarding internal consistency, convergent and divergent validity, and test-retest reliabilities, proving to be a psychometrically sound measure within the Portuguese population. Study 4 had multiple purposes, including (1) the creation of categories of micro events related to customers’ behavior in call-centers, (2) ascertaining the influence of such events on workers’ emotions, controlling for their susceptibility for contagion (using the Portuguese version of the emotional contagion scale validated on study 3); and (3) to verify the impact of such emotions, experienced daily, on turnover intentions and cardiovascular efficiency. Main results supported that customer related events were significant precursors of affective experiences at work, and that susceptibility for contagion influenced this relation. Results also supported the influence of emotions on turnover and health, with a superior contribution of fear in explaining both outcomes.